واقع الممارسة الارشادية في المدارس المتوسطة من وجهة نظر المرشدين التربويين في مدينة - بلقاسم كشنة; سهام بوخرص; عائشة بدوي (My University, 2021)
This study was represented in revealing the reality of the guiding practice from the point of view of the guidance counselors. The study was conducted on a sample of guidance counselors with averages of the municipality of Laghouat, which numbered 14 average, and the sample was estimated at 14 advisors The questionnaire was used as a data collection tool We started with the following question: What is the reality of guiding practices from the point of view of guidance counselors in the intermediate stage? The research revolved around 4 sub-hypotheses: There are a number of obstacles related to (personal preparations, professional and academic preparation, the professional environment, the legislative and legal aspect), which impede the practice of counseling programs for psychological and educational guidance and counseling. There are no statistically significant differences between school guidance counselors in the obstacles to counseling practice due to the gender factor There are no statistically significant differences between the counseling guidance counselors in the obstacles to counseling practice due to the academic preparation factor. There are no statistically significant differences between school guidance counselors in the obstacles to counseling practice due to the professional experience factor. We have reached several results, the most important of which are: - We found out from the results of the first hypothesis that the consultants see that most of the obstacles that existed previously have been overcome and the work atmosphere has become conducive to the performance of the guiding task. As for the second hypothesis, it was found that the null hypothesis is true and that the gender factor does not constitute a problem in the practice of the counseling process As for the third hypothesis, we also found out the validity of the null hypothesis, meaning that all the disciplines required for the profession of guidance counselor do not have differences or any obstacles attributed to the specialization As for the fourth hypothesis, the null hypothesis was also fulfilled, meaning that the professional experience factor for consultants does not necessarily lead to problems at work, as newcomers to work are like those with long experience, but only relatively, and this hypothesis in particular needs deeper research.Reality of Guiding Practices, guidance counselors, Educational guidance and counseling programs